Development of The Semarang Bridge Fountain as The Newest Tourism Destination in Semarang - Damiasih Damiasih; Asalia Maharani Ochta Brilian (Jayapangus Press, 2023)
The development of increasingly competitive tourism to boost regional income and grow the economy from the tourism sector certainly opens up space to explore regional potential through tourism development, one of which is the development of the Semarang bridge fountain as the newest tourist destination in Semarang, Central Java, which is interesting to study. The purpose of this research is to develop bridge fountain tourism and to know the Semarang government's strategy for developing bridge fountains and how the role of the community in tourism development. This research uses a qualitative research model. The results of this study found that in the development of a bridge fountain, there are two factors, namely internal and external, internal factors consist of: 1) manager or organization, 2) human resources, 3) relations between human resources, 4) accessibility, 5) facilities, 6) potential and 7) funding. While external factors consist of 1) regulation, 2) competitors, 3) tourists, 4) market share, 5) technology, and 6) promotion. From the results of the study it can be concluded Semarang Bridge Fountain is the newest tourist destination in Semarang City which is managed by the government, namely the Semarang City Public Works Department by presenting its main potential, namely dancing fountains. The Semarang City Public Works Service has created a team of Semarang Bridge Fountain (SBF) Field Officers who are always on guard at the location and have good communication relationships and the Semarang Bridge Fountain is in a strategic location. But it is very unfortunate because there is no cooperation with the surrounding community, the facilities that are owned are still lacking and requires the development of dancing fountains so that they are not boring.